Synthesis of CaCO3@C yolk–shell particles for CO2 adsorption1. Issue 32 (10th April 2015) - Boyjoo, Yash; Merigot, Kelly; Lamonier, Jean-François; Pareek, Vishnu K.; Tade, Moses O.; Liu, Jian
<x xml:space="preserve">Abstract</x> This paper reports the first example of the synthesis of CaCO3@C yolk–shell particles and their application in CO2 adsorption.